Treatment of Patient with Recurrent Major Depressive Disorder: A Case Report - Mahalle, Mohammed (HM Publisher, 2024)
Introduction: The alteration of biogenic amines, in particular norepinephrine and serotonin, is a hypothesis that is frequently put forward in relation to the etiology of major depressive disorder. This study was aimed to present the recurrent major depressive disorder in a forty years old woman. Case presentation: A 40-year-old woman, presented to our mental health unit with symptoms of a low mood, which she described as similar to previous episodes of depression. Two decades ago, she underwent an evaluation and received a diagnosis of severe depression for the first time. Throughout that duration, she received imipramine (tricyclic antidepressant/TCA) at dosages of up to 150 mg per day, resulting in favorable outcomes. She claimed that she abstained from illicit substances and has not undergone any distressing events in the recent past. Although she was confident that she was experiencing another severe depression, she expressed a desire to avoid using imipramine this time due to its adverse effects, including dry mouth, dry eyes, and diarrhea. The patient was diagnosed as recurrent major depressive disorder without psychotic symptoms. Conclusion: The likelihood of experiencing additional bouts of major depression is higher when there have been multiple prior episodes, residual symptoms of depression between episodes, and the coexistence of other psychiatric or chronic medical conditions. Prior episodes of serious depression that responded well to treatment have a greater probability of reaching remission in future episodes. First-line treatment options for major depressive disorder include selective serotonin reuptake inhibitors (SSRIs) such as bupropion, venlafaxine, mirtazapine, and duloxetine.